Domestic abuse treatment perspective that builds client voice and skills in a court-ordered environment. Issue 3 (3rd July 2019) - Chovanec, Michael G.
ABSTRACT: Building client voice in men who abuse to reduce dropout and improve outcomes in domestic abuse treatment continues to challenge. This mixed-method study examined the implementation of the Outcome Rating Scale (ORS), a client feedback tool, as a component of an open-ended group domestic abuse program (N = 25). Additionally, the Social Empathy Index (SEI) was administered during pre- and posttreatment individual interviews. Further information about the treatment experience was gleaned from interviews of three treatment completers. More than three fourths of the participants (21 or 84%) completed the minimum of 18 weeks, more than one third (8 or 38%) of completers showed reliable or clinically significant change on the ORS, with a statistically significant increase on the SEI reflecting increases in empathy concurrent with their view of making progress in treatment. Building awareness of self and others' points of view and applying relationship enhancement skills were key themes expressed during interviews.